Fast co‐evolution of anti‐silencing systems shapes the invasiveness of Mu‐like DNA transposons in eudicots. (14th March 2022) - Sasaki, Taku; Ro, Kyudo; Caillieux, Erwann; Manabe, Riku; Bohl‐Viallefond, Grégoire; Baduel, Pierre; Colot, Vincent; Kakutani, Tetsuji; Quadrana, Leandro
Abstract: Transposable elements (TEs) constitute a major threat to genome stability and are therefore typically silenced by epigenetic mechanisms. In response, some TEs have evolved counteracting systems to suppress epigenetic silencing. In the model plant Arabidopsis thaliana, two such anti‐silencing systems have been identified and found to be mediated by the VANC DNA‐binding proteins encoded by VANDAL transposons. Here, we show that anti‐silencing systems have rapidly diversified since their origin in eudicots by gaining and losing VANC‐containing domains, such as DUF1985, DUF287, and Ulp1, as well as target sequence motifs. We further demonstrate that these motifs determine anti‐silencing specificity by sequence, density, and helical periodicity. Moreover, such rapid diversification yielded at least 10 distinct VANC‐induced anti‐silencing systems in Arabidopsis . Strikingly, anti‐silencing of non‐autonomous VANDAL s, which can act as reservoirs of 24‐nt small RNAs, is critical to prevent the demise of cognate autonomous TEs and to ensure their propagation. Our findings illustrate how complex co‐evolutionary dynamics between TEs and host suppression pathways have shaped the emergence of new epigenetic control mechanisms. Synopsis: Transposable elements (TEs) can escape their typical fate of epigenetic silencing through still poorly‐understood mechanisms. Systematic characterization of VANDAL transposon‐encoded anti‐silencing systems in A. thaliana sheds light on the co‐evolutionary dynamics that lead to novel epigenetic control mechanisms. VANDAL ‐encoded VANC anti‐silencing proteins paredate the radiation of eudicots and exhibit rapid diversification through gain/loss of domains and target short‐sequence motifs. Sequence, density, and helical periodicity of motifs within non‐coding regions of VANDAL s determine VANC targeting. Non‐autonomous VANDAL elements hijack the anti‐silencing mechanisms of related autonomous VANDAL s to promote their own hypomethylation. Loss of target motifs within non‐autonomous elements can induce concerted epigenetic re‐silencing of related VANDAL s, potentially self‐limiting runaway transposon proliferation. Abstract : Targeting of VANC anti‐silencing proteins is determined by sequence, density, and helical periodicity of sequence motifs within non‐coding regions of VANDAL elements.